La pertinencia de la enseñanza del sánscrito en el plan de estudios de filología clásica - Argüello Scriba, Sol (2012)
The presence of the Sanskrit language in Philology, is recent in the West. However, it´s arrival causes great changes in Philology, including the birth of language studies. It also changed the idea that the origin of every language was in the Tower of Babel´s myth in the Old Testament. Comparative methods arise in the literature,language, mythology, that are still in force.